(untitled) (Journal of Engineering, 2013)
The study presents the test results of Completely Decomposed Granite (CDG) soil tested under drained triaxial compression, direct shear and simple shear tests. Special attention was focused on the modification of the upper halve of conventional Direct Shear Test (DST) to behave as free head in movement along with vertical strain control during shear stage by using Geotechnical Digital System (GDS). The results show that Free Direct Shear Test (FDST) has clear effect on the measured shear stress and vertical strain during the test. It has been found that shear strength parameters measured from FDST were closer to those measured from simple shear and drained triaxial compression test. This study also provides an independent check on the consistency of the data by providing an interpretation for angle of dilation together with shearing resistance by using flow rule analysis